Kinerja Green Supply Chain Management Dilihat Dari Aspek Reverse Logistic dan Green Procurement pada UKM Kuliner di Kota Palembang - Heriyanto Heriyanto; Andrian Noviardy (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2019)
The study aims to determine the performance of Green Supply Chain Managament viewed from the aspect of Reverse Logistics and Green Procuretment In Culinary Ukm Dikota Palembang.pada Culinary SME Palembang City.As a city that has a wealth of diverse culinary, culinary SMEs are expected to participate in supporting environmentally sound development. This is because the concept of Green Supply Chain Management (GSCM) is a concept that aims to minimize the negative impact of an organization and its supply chain on the environment related to climate change, pollution and non-renewable resources. In order to support GSCM, it is necessary to evaluate the extent to which this concept is carried out by Culinary SMEs in Palembang City. This evaluation is expected to identify the constraints and barriers facing SMEs in doing GSCM. By conducting a survey of 36 culinary SMEs, it was found that culinary SMEs in Palembang City have not implemented GSCM practices. This can be seen from the low mean value. Therefore, there needs to be support from related parties in this case the government to conduct socialization and dive and assistance in GSCM.